The construction and validation of the OASys violence predictor: advancing violence risk assessment in the English and Welsh correctional services - Howard, Philip D. (Criminal justice and behavior, 2012)
The Offender Assessment System (OASys) is the risk assessment and management system routinely used in the National Offender Management Service (NOMS), the prison and probation service for England and Wales. This study describes the construction and validation of a new actuarial violence risk measure, the OASys Violence Predictor (OVP), using OASys and Police National Computer data. Ordinal logistic regression identifies static and dynamic risk factors predictive of violent recidivism among convicted offenders (N = 15,918). These form the basis of a user-friendly 100-point scale (OVP). OVP achieves significantly greater predictive validity than existing actuarial scores available within NOMS (the original OASys risk prediction score; the Offender Group Reconviction Scale, Version 3; and the V scale of the Risk Matrix 2000) on a later validation sample (N = 49,346). The discussion considers explanations for this improvement, examines the utility of dynamic risk factors in violence prediction, and describes the application of OVP in the NOMS treatment allocation and risk management practice.